Стратегія розвитку виробництва та переробки зерна кукурудзи як шлях вирішення енергетичної незалежності та безпеки України - Полішкевич, О. Р.; Polishkevich, Olga (КНТУ, 2015)
У статті наведені результати досліджень щодо ефективності використання основних сільськогосподарських культур для виробництва біопалива. Виявлено найефективнішу культуру для переробки. Розрахована ефективність переробки кукурудзи на етанол. Обґрунтовано проект будівництва заводу з виробництва біоетанолу. Запропонована стратегія розвитку виробництва та переробки зерна кукурудзи. Досліджений стан та економічна ефективність виробництва кукурудзи при врахуванні конкурентоспроможності, рівня цін та прибутковості галузі. The aim is to conduct research that focus on evaluating the effectiveness of using corn as a feedstock for biofuel production in Ukraine. The article presents the results of studies on the efficiency of plant crops for biofuels. The effective culture for recycling. Calculated efficiency of processing of corn for ethanol. Reasonably project to build a bioethanol plant. Offered strategy of development of production and processing of grain of corn. Investigational state and economic efficiency of production of corn at the account of competitiveness, standard of prices and profitability of industry. At today's fuel prices is clear that for Ukraine to produce ethanol from corn is beneficial for both domestic consumption and for its exports.
Strategy of development of production and processing of corn as a way to solve the energy independence and security of Ukraine
Keywords: кукурудза; потенціал забезпечення; біоетанол; економічна ефективність; енергетичні ресурси; corn; potential of providing; bioethanol; economic efficiency; power resources